Isodicentric Yq mosaicism presenting as infertility and maturation arrest without altered SRY and AZF regions - Lehmann, Kyle J. (Springer US, 2012)
The isodicentric Y (idic Y) chromosome is one of the most common aberrations of the human Y chromosome. Due to a structural instability during cell division, patients with idic Y may develop mosaic karyotypes with variable phenotypes. We present a rare case of a 25-year-old male with azoospermia and infertility. In this patient, an idic Yq was characterized by duplication of almost the entire Y chromosome in head-to-head fashion with breakpoints occurring at the distal Yp / Yp11.3 with sparing of both the AZF and SRY regions. We discuss the possible mechanisms of azoospermia in this patient and add to the limited evidence that exists regarding the importance of pseudoautosomal regions and meiotic sex chromosome pairing as part of normal spermatogenesis.